2019
DOI: 10.1002/pbc.28006
|View full text |Cite
|
Sign up to set email alerts
|

Universal screening for social determinants of health in pediatric sickle cell disease: A quality‐improvement initiative

Abstract: Background Social determinants of health (SDoH) are socioeconomic factors that influence health outcomes. Guidelines recommend universal screening for SDoH at clinic visits; however, models that do not require additional resources are limited in subspecialty clinics. Individuals with sickle cell disease (SCD) face the burdens of chronic illness and often racial disparities, both of which may increase their vulnerability to adverse SDoH. Hematologists can impact both quality of life and clinical outcomes for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 20 publications
4
92
0
Order By: Relevance
“…Caregivers’ “habit” of accessing support for basic needs through the SCD clinic speaks to a larger societal problem of systemic inequity and lack of a sufficient safety net that makes navigating services difficult—a process further exacerbated by managing a complex chronic illness. Assumptions about caregivers’ lack of self-sufficiency are contradicted by research in an urban pediatric hematology clinic, which demonstrated that 45% of families provided with a community referral had communicated with the community agency within 2 weeks of receiving the referral [ 9 ]. However, when help is offered, families may be reluctant to accept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers’ “habit” of accessing support for basic needs through the SCD clinic speaks to a larger societal problem of systemic inequity and lack of a sufficient safety net that makes navigating services difficult—a process further exacerbated by managing a complex chronic illness. Assumptions about caregivers’ lack of self-sufficiency are contradicted by research in an urban pediatric hematology clinic, which demonstrated that 45% of families provided with a community referral had communicated with the community agency within 2 weeks of receiving the referral [ 9 ]. However, when help is offered, families may be reluctant to accept.…”
Section: Discussionmentioning
confidence: 99%
“…These sites serve as critical settings for such interventions given their typically centralized locations and capacity to have the resources to serve broad catchment areas. Yet, despite the demonstrated needs of the patient population [ 6 , 9 ], similar SDoH screening and referral models have not been as widely investigated or implemented in pediatric subspecialty care. Our study addresses this significant gap in the literature by assessing urban pediatric hematology clinic staff’s perspectives regarding barriers and facilitators to addressing unmet basic needs experienced by families with a child with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…The SDoH screener is a self‐reported, paper questionnaire completed by the families of patients with SCD during pediatric hematology clinic appointments. It was initiated during a quality improvement study to implement a validated screening for SDoH into our clinic for patients with SCD and to connect families in need with appropriate community resources 26 . Between August 2017 and June 2019, 83% of patients of all ages with SCD who had visited the hematology clinic in the study period had completed a screener (142 of 171).The pediatric hematology clinic serves approximately 180 patients with SCD from birth through 21 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…Assumptions about caregivers' lack of self-su ciency are contradicted by research in an urban pediatric hematology clinic, which demonstrated that 45% of families provided with a community referral had communicated with the community agency within two weeks of receiving the referral. 9 However, when help is offered, families may be reluctant to accept. In a study of caregivers' perspectives on provider assistance with community services, caregivers expressed feeling judged by those providing services, which compromised their motivation to contact and enroll in resources.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite the demonstrated needs of the patient population, 6,9 similar SDoH screening and referral models have not been as widely investigated or implemented in pediatric subspecialty care. Our study addresses this signi cant gap in the literature by assessing urban pediatric hematology clinic staff's perspectives regarding barriers and facilitators to addressing unmet basic needs experienced by families with a child with SCD.…”
Section: Introductionmentioning
confidence: 99%